BEST PARENTING-PARENTS TO DIET AND FOOD-CONSUMPTION ON TODDLERS - Heri Bahtiar; Maelina Ariyanti; Aswati Aswati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. There are 103 toddlers in West Lombok suffering from severe malnutrition throughout 2013. This regency is ranked as the second place out of ten districts/cities in NTB having severely malnourished. It is due to the fact that illness and parenting-parents have yet been considered. The purpose of this study was to analyze relationship parenting-parent with diet and toddlers food consumption.Method. This study used analytical observation research with Cross-sectional design. The population were the entire households having children at Banyu Urip village with the samples, eighty-one toddlers, were taken through random sampling technique. Its data was analyzed by using Spearman Rank. Result. The finding shows; 1) parenting-parents, most authoritarian, is 47 (58%); 2) diet toddler, good category, is 58 (71.6%); 3) food-consumption on toddlers, deficit category, is 27 (33.3%); 4) no relationship among the parenting-parents, diet (p= 0.095) and toddler food consumption (p = 0.17). Discussion. Thus, it can be inferred that an authoritarian-parenting is the best parenting to diet and food-consumption for toddler-malnutrition.Key words: Parenting, Diet, Food-consumption, Toddler